Improving Students' Learning by Involving Them in the Design of the Course - Correa, Doris (Íkala, Revista de Lenguaje y Cultura, 1998)
This collaborative learning experience narrates how a group of university students was involved in the design of their course and how they also took part in evaluating the results of this process. To do so, they had to reflect back upon the decisions made and discuss which actions had the best effects and why.